Self-efficacy, religiosity, and crime: profiles of African American youth in urban housing communities - Lombe, Margaret (Victims & offenders, 2017)
Youth reporting independently elevated levels of religiosity and self-efficacy tend to abstain from externalizing behavior. However, little is known about the ways in which religiosity and self-efficacy interrelate to impact youth externalizing. Drawing from a sample of African American youth from public housing communities (N = 236), we use latent profile analysis to identify subtypes of youth based on self-reported religiosity and self-efficacy and, in turn, examine links with crime. Compared to youth in other subgroups, those classified as both highly religious and highly self-efficacious reported less involvement in minor and severe delinquency, but not violence.R25 DA030310 - National Institute on Drug Abuse; R25 DA030310 - National Institutes of Healt